2020
DOI: 10.1016/j.diabres.2020.108263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19 hospitalized patients with diabetes in the United Kingdom: A retrospective single centre study

Abstract: To describe the clinical characteristics and outcomes of hospitalized COVID-19 patients with diabetes. Methods: A retrospective cross-sectional study was conducted among patients admitted to the William Harvey Hospital in England between March 10th and May10th, 2020 with a laboratory-confirmed severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), known as COVID-19. Variation in characteristics, length of stay in hospital, diabetes status, duration of diabetes, control of diabetes, comorbidities and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
93
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 17 publications
21
93
3
3
Order By: Relevance
“…10,11 It can be seen that it was not the fact of being hospitalized in a public or private institution that determined the 'death' outcome but rather health status prior to being admitted to hospital, including comorbidities associated with COVID-19, such as tobacco use disorder, diabetes mellitus, hypertension and obesity, among others. 12,13 Tobacco use disorder, for instance, as a behavior recognized as being more prevalent among the low-income Brazilian population, 14 was found to be more prevalent in individuals notified by public institutions. It is possible that tobacco use disorder may contribute to worse COVID-19 progression, given that besides harm to the lungs the habit of smoking is associated with cardiovascular disease, including predisposition to thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…10,11 It can be seen that it was not the fact of being hospitalized in a public or private institution that determined the 'death' outcome but rather health status prior to being admitted to hospital, including comorbidities associated with COVID-19, such as tobacco use disorder, diabetes mellitus, hypertension and obesity, among others. 12,13 Tobacco use disorder, for instance, as a behavior recognized as being more prevalent among the low-income Brazilian population, 14 was found to be more prevalent in individuals notified by public institutions. It is possible that tobacco use disorder may contribute to worse COVID-19 progression, given that besides harm to the lungs the habit of smoking is associated with cardiovascular disease, including predisposition to thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the knowledge that patients with DM feature greater odds for death due to infection compared to non-diabetic patients, it may be deduced that the complication with an acute hyperglycemic crisis will further worsen overall prognosis [1]. However, according to a recent retrospective analysis from the UK, patients with DM who develop DKA due to disease are more likely to survive compared to those patients that are not complicated by an acute hyperglycemic crisis [5].…”
Section: Dear Editormentioning
confidence: 99%
“…Case-control studies conducted on COVID-19 during the pandemic concluded that comorbidity (persistence of medical conditions including obesity, hypertension and diabetes mellitus) could be a determinant on the progression of COVID-19 in individuals [10]. Although the data is quite limited, recent studies have put forward that the prevalence of diabetes mellitus (DM) and elevated blood glucose levels can act as independent factors of mortality and morbidity related to COVID-19; firstly because individuals with diabetes have a prolonged recovery duration from viral diseases due to having a compromised immune system and secondly for the virus's ability to sustain itself in an environment with high glucose levels putting individuals with diabetes mellitus at a vulnerable position from the aspect of casualties due to COVID-19 [11][12][13].…”
Section: Introductionmentioning
confidence: 99%